A Prática (In)Formada por Evidências face a formação do Professor de Matemática The practice (in)formed by evidences towards the mathematics teacher education - Silva, Marcos Guilherme Moura; Gonçalves, Tadeu Oliver; Malheiro, João Manoel da Silva (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2014)
O movimento rumo à Prática Baseada em Evidências é tão importante quanto polêmico. Sua ampla difusão na área médica e em campos afins figura no cenário educacional como uma discussão contemporânea. O presente estudo teve como objetivo investigar em que aspectos a Prática Baseada em Evidências (PBE) pode contribuir enquanto processo de formação continuada do professor de Matemática. Para tanto, trilhou-se os caminhos de uma pesquisa qualitativa. As análises se pautaram na Teoria da Aprendizagem Transformadora proposta por Jack Mezirow (2013) e nas considerações teóricas de Bosh e Gascon (2001). Os resultados apontam, dentre outras contribuições, que a experiência formativa desenvolvida se constitui como alicerce de Aprendizagem Informacional e Transformacional, nos termos propostos por Mezirow (2013). The movement towards evidence-based practice is as important as controversial. Its wide diffusion in the medical field and in related fields appears in the educational scene as a contemporary discussion. The present study, which consists on a piece of the research developed during academic master, aimed at investigating in what aspects the Evidence-Based Practice (EBP) can contribute while process of continuous education of mathematic teachers. In order to do so, based on Transformative Learning Theory proposed by Jack Mezirow (2013) and on theoretical considerations of Bosh and Gascon (2001), we decided for a qualitative research. The results showed us that it was an opportunity for an active teacher education. In addition, it highlighted the professional judgment related to practice itself and the resulting practices of scientific research. It also encouraged the investigation for acquiring knowledge and narrowed basic education teacher relations with the systematic research of mathematics education according to Mezirow (2013) proposed terms.